2020
DOI: 10.37669/milliegitim.787959
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenleri̇n Uzaktan Eği̇ti̇me İli̇şki̇n Görüşleri̇

Abstract: COVID-19 salgını nedeniyle tüm dünyada ve ülkemizde en çok kullanılan eğitim yöntemi haline gelen uzaktan eğitim sürecini öğretmen görüşlerine göre incelemeyi amaçlayan bu çalışma ile öğretmenlerin görüşleri ile ilgili toplanacak verilerin ileride yürütülecek uzaktan eğitim uygulamalarına yön vermesi amaçlanmaktadır. Bu araştırma için nitel ve nicel araştırma yöntemlerinin bir arada kullanıldığı karma yöntem deseni kullanılmıştır. Bu araştırmanın çalışma grubunu farklı il/ilçelerde koronavirüs sebebi ile uzakt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 20 publications
2
10
0
13
Order By: Relevance
“…Moreover, there was no significant difference in the DEPT scores of teachers according to gender, grade level taught and years of experience. This result is consistent with the results of Kurnaz et al (2020) who revealed that there is no significant difference in distance education perceptions of teachers according to the aforementioned variables. In addition, this result is incompatible with the results of some studies that argue males have more positive perceptions than females about online learning, which is an important element of distance education (Markauskaite, 2006;Ong & Lai, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, there was no significant difference in the DEPT scores of teachers according to gender, grade level taught and years of experience. This result is consistent with the results of Kurnaz et al (2020) who revealed that there is no significant difference in distance education perceptions of teachers according to the aforementioned variables. In addition, this result is incompatible with the results of some studies that argue males have more positive perceptions than females about online learning, which is an important element of distance education (Markauskaite, 2006;Ong & Lai, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…To determine the mathematics teachers' views on distance education "Distance Education Perceptions of Teachers Scale (DEPT)" developed by Kurnaz et al (2020) was used. The instrument consists of 37 items in a five-point Likert type ranging from "strongly agree" to "strongly disagree".…”
Section: Instrument and Data Collection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…• Bu çalışmada nicel araştırma yöntemleri kullanılsa da nitel araştırma yöntemlerinin kullanılarak öğretmen görüşlerinin daha derinlemesine ele alındığı farklı çalışmalar yürütülebilir. in the scores of teachers' attitude towards distance education according to gender (Ağır, 2007;Horzum, 2003;Kuşkonmaz, 2011;Tırnovalı, 2012;Ülkü, 2018), in some studies, this difference is in favor of female teachers (Alea, Fabrea, Roldan, & Farooqi, 2020;Kurnaz, Kaynar, Şentürk-Barışık, & Doğrukök, 2020). For this study, one of the reasons for the different result may be the significant difference between the number of male and female teachers.…”
Section: öNeri̇lerunclassified
“…Öztürk ve Çetinkaya (2021) televizyon izlenme oranlarını inceleyerek öğrencilerin uzaktan eğitim sürecinde Eba Tv'ye yoğun ilgi gösterdiğini tespit etmiştir. Kurnaz, Kaynar, Şentürk Barışık ve Doğrukök (2020) de Eba Tv derslerinin öğrencilerin dikkatini toplayamadığını belirtmişlerdir. Yabancı uyruklu öğrencilerin evlerinde kimi zaman Türk kanal sistemi kurulu olmadığından, yabancı uyruklu öğrenciler Trt Eba Tv'ye ulaşmakta güçlük yaşayabilir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified